THE EFFECT OF USING EXPERIENTIAL LEARNING METHOD ON THE SPEAKING SKILLS OF CLASS XI STUDENTS OF SMK PP NEGERI KUTACANE ACEH TENGGARA ACADEMIC YEAR 2022/2023 - Saiba Harianti Putri; Raja Fauziah; Wikiaprian Pinim (STKIP USMAN SAFRI KUTACANE, 2024)
Speaking skills are the most important part of learning a foreign or second language. In addition, the success of language learning is measured by the demonstrated ability to converse in the target language. Skills speaking is an interactive process of constructing meaning which includes generating, receive, process and use both verbal and non-verbal components. The weaknesses of the students of SMK PP Negeri Kutacane in learning English so far, especially in speaking English skills are very weak and of course this weakness is caused by something complex, without ignoring various factors, the author feels the need to conduct research with the title above so that it can be known whether students' interest in learning increase or not when using the experiential method. The population sampled was class XI SMK PP Negeri Kutacane. In this study, the researchers used an Experiential Learning method to determine the significant effect of the application of the experiential learning method on students' speaking skills, stating that quantitative research uses numbers, starting from data collection, interpretation of data, and the appearance of data results. Based on the calculation above, the research found that t stat > t critical, or 13,74 > 1,69 so that H0 is rejected and H1 is accepted. Therefore, there is an effect of using the experiential learning method on the speaking skills of class XI students of the SMK PP Negeri Kutacane Aceh Tenggara academic year 2022/2023. The conclusions obtained from the results of this study are as follows: there is an effect of using the experiential learning method on the speaking skills of class XI students of SMK PP Negeri Kutacane Aceh Tenggara academic year 2022/2023.